2014
DOI: 10.1007/s10103-014-1704-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a new infrared laser transillumination technology (808 nm) for the detection of occlusal caries—an in vitro study

Abstract: This study aimed to evaluate in vitro performance of near-infrared laser transillumination (NIR-LTI) for detecting early occlusal caries in permanent teeth and compare it with quantitative light-induced fluorescence (QLF), DIAGNOdent Pen (DDPen), and conventional radiography (CR). Ninety-four occlusal surfaces presenting International Caries Detection and Assessment System (ICDAS) scores ranging from 0 to 3 were selected. For the NIR-LTI examination, images were captured using a prototype, which consists of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 37 publications
2
20
1
2
Order By: Relevance
“…Of the 27 articles included, 23 used DIAGNOdent [3,4,, studying sensitivity, specificity and AUC in vitro in 16 of them [4,[7][8][9][10][11][13][14][15][16][17]20,[23][24][25][26] while nine were in vivo [3,12,16,18,19,21,22,26,27]; in two cases, however, (Theocharopoulou 2015 [21] and Peycheva 2016 [24]) carried out the study in vivo and in vitro. For VistaProof, 14 articles were reviewed [4,5,7,8,10,12,14,15,19,23,[27][28][29][30], of which 10 were in vitro [4,7,8,10,14,15,23,…”
Section: The Qualitative Analysismentioning
confidence: 99%
“…Of the 27 articles included, 23 used DIAGNOdent [3,4,, studying sensitivity, specificity and AUC in vitro in 16 of them [4,[7][8][9][10][11][13][14][15][16][17]20,[23][24][25][26] while nine were in vivo [3,12,16,18,19,21,22,26,27]; in two cases, however, (Theocharopoulou 2015 [21] and Peycheva 2016 [24]) carried out the study in vivo and in vitro. For VistaProof, 14 articles were reviewed [4,5,7,8,10,12,14,15,19,23,[27][28][29][30], of which 10 were in vitro [4,7,8,10,14,15,23,…”
Section: The Qualitative Analysismentioning
confidence: 99%
“…It was believed that this variation in longitude of wavelength of light would have a promising effect in terms of the detection of early-stage carious lesions, as it had been shown that light with the said characteristics disperses itself less and hence is able to penetrate more deeply in dental tissue, thereby enabling a better transmission of light, offering hence a considerable benefit [6][7][8]. This method entails, according to the absorption and dispersion of light, a good contrast between carious areas and those healthy areas surrounding the lesion, facilitating detection.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of DIAGNO dent, in detecting secondary caries under composite restorations, is reported to be similar to digital radiographs [17], however, the Cone beam computed tomography seemed to represent the best accuracy [18]. Near-infrared laser transillumination (NIR-LTI) is another new generation of caries detectors which have shown promising results compared to DIAGNOdent however the researches are not vast enough to make a determined conclusion [19]. …”
Section: Materials and Methodologymentioning
confidence: 99%